SOSIALISASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) PADA GURU KELAS DI MI NURUL HUDA PULAU BATU - Angel Sophia Intan; Riski Maulana; Endang Sukinah; Riko Saputra; Meta Yupitri Zoningsih; Ahmad Syai’un; Aqilatunnazia Aqilatunnazia (LPPM Institut Pendidikan Nusantara Global, 2025)
Education is a lifelong learning process essential for developing individual potential. However, at MI Nurul Huda Pulau Batu, the learning process still relies heavily on a teacher-centered model using lectures, resulting in low student engagement and participation. To address this issue, a socialization and training program on the Cooperative Learning Model, specifically the Group Investigation (GI) type, was conducted for teachers at MI Nurul Huda Pulau Batu. This model encourages students to actively learn in heterogeneous groups, fostering creativity, communication skills, and social responsibility. The training utilized lectures, question-and-answer sessions, and practical demonstrations. The results indicate an increased understanding among teachers regarding the GI model and its potential to create a more active and enjoyable learning environment. Although the training time was limited, the activity contributed positively to enhancing teacher competencies and is expected to improve the overall quality of learning at MI Nurul Huda Pulau Batu.